Meningkatkan Kesadaran Keamanan Siber di Era Digital: Mitigasi Penipuan Online dan Hoaks Bagi Karyawan Politeknik LP3I Cirebon - Aris Riyanto; Melva Drummeron; Nindy Ayu Putri; Chantiqa Audrieya Cahya; Abdul Bashit (LPPM POLITEKNIK LP3I, 2024)
This outreach and research initiative discusses the implementation of an interactive seminar on digital literacy at Politeknik LP3I Kampus Cirebon, focusing primarily on online fraud, hoaxes, and cyber attacks. The seminar was conducted using a hybrid approach, combining face-to-face sessions and online platforms via Google Meet to facilitate participation without geographical limitations. The seminar was divided into two main sessions: the first on online fraud, and the second session discussing hoaxes; their general understanding, characteristics, and tools for identifying and avoiding fake news. Each session was interactive, allowing participants to directly engage with speakers and practice using the tools provided. From the survey results distributed to participants, it was found that the satisfaction rating for the seminar's quality was 4.89 out of a maximum of 5. Additionally, 95% of participants reported an increase in understanding and confidence in digital literacy, particularly in dealing with online fraud, hoaxes, and other cyber threats. This demonstrates the effectiveness of an interactive approach and focusing on current issues like cybersecurity in enhancing awareness and readiness among campus employees.